Buddhist monks and monasteries of India : their history and their contribution to Indian culture - Dutt, Sukumar (George Allen and Unwin, 1962)
Part I : The Primitive Sangha -- Part 2 : The Asoka-Satavahana Age (250 BC-AD 100) and itsLlegacy -- Part 3 : In the Gupta age (AD300-550) and After -- Part 4 : Eminent monk-scholars of India -- Part 5 : Monastic Universities (AD500-1200)